Mitigation of Fluoride Contamination from Drinking Water through Fluoride Removal Techniques: A Review - Yadav, Sucheta (International Journal of Humanities and Education Development (IJHED), 2023)
Water is the most vital natural resource for the survival of human being and environment on the earth surface. But Fluoride contamination of water has become a widespread and serious problem all over the world including India. Supplying the right amount of fluoride to drinking water protects the teeth from decay and reduces the risk of cavities. Exposure to fluoride beyond the recommended level for longer duration causes both dental and skeletal fluorosis. Health is the most important issue for the citizens of any country and consequently healthy citizens are the perfect and biggest assets for a nation. This paper reveals the techniques of Eradication of excessive fluoride from water. Various alleviation programmes and strategies to regulator the fluorosis and to eliminate the fluoride from water have been piloted all over the world using defluoridation. Nalgonda procedure is one of the well-known strategies generally utilized for defluoridation of water as a part of developing nations, for example, India, Kenya, Senegal and Tanzania. Among different techniques utilized for defluoridation of water, the adsorption procedure is broadly utilized.